The Role of Geographical Factors in the Strategy of Selecting Expansion Areas in the Roman Period: The Role of Geographical Factors in the Strategy of Selecting Expansion Areas in the Roman Period (Elmergib Journal of Human Sciences, 2026)
Following the consolidation of Roman power in the Mediterranean basin, the Romans adopted a series of strategic policies aimed at strengthening and expanding their civilization. Among the most significant of these strategies was the deliberate selection of areas for territorial expansion in accordance with the political, economic, and strategic interests of the Roman Empire. In this context, geographical factors played a decisive role in determining the suitability of regions for settlement, development, and long-term sustainability ,This study examines the role of geographical determinants in the Roman strategy of site selection through a comparative analysis of two important urban centers in the province of Tripolitania: the coastal city of Leptis Magna and the inland semi-desert city of Ghirza. The research classifies these determinants into two main categories. The first includes natural geographical factors, such as location, topography, water resources, and climate. The second encompasses economic and human factors, including agriculture, industry, and trade.
Keywords: Leptis Magna; City of Ghirza; Geographical and Economic Factors; Expansion Areas